The Role of Islamic Boarding Schools in Enhancing Adolescents' Resilience to Moral Crises in Sapeken District - Habib; Hayumuti; Asrori (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
Sapeken District is a remote archipelagic area with limited transportation access and educational infrastructure, resulting in unequal youth development services. Low public awareness of the importance of education further exacerbates adolescents’ vulnerability to the negative impacts of globalization and unfiltered information technology. In recent years, moral degradation among adolescents in this region has intensified due to weak value-based guidance and limited moral supervision. This study aims to analyze the role of Abu Hurairah Islamic Boarding School in strengthening adolescents’ moral resilience in Sapeken District, Sumenep Regency. The research employs a qualitative descriptive approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving teachers, students, and relevant stakeholders. The findings reveal that Abu Hurairah Islamic Boarding School plays a strategic role in enhancing adolescents’ moral resilience through intensive religious education, exemplary role modeling by teachers and caregivers, personal mentoring approaches, and the enforcement of firm rules and sanctions against deviant behavior. These efforts effectively foster adolescents’ moral resilience and promote the internalization of moral values in dailylife.